A presença da família camponesa na escola família agrícola : o caso de Olivânia - Caliari, Rogério (2013)
This research examines relations between peasant families and the Agricultural Family School located in the Valley of the Coryndiba River, in the municipality of Anchieta, Espírito Santo, Brazil. It was developed along the research line of the Culture, Curriculum and Teacher Training of the Graduate Program in Education of the Federal University of Espírito Santo. It discusses how the moments of participation by peasant family in the pedagogy of Alternation are constituted, and more specifically their presence in educational practices in this educational institution. Theoretical and practical aspects regarding participation are discussed (Santos Guerra, 2002; Gimonet 2007; García-Marirrodrga e Puig-Calvó, 2010 e; Duffaure, 1993 ). It also deepens discussions about "peasant ethos" (Brandão, 1995, 1995a, 1999 e; Woortmann, 1990a, 1997). The qualitative approach to education made it possible to explore methodological issues of socio-anthropological research (Da Matta,1987; Brandão, 2003 e; Fichtner et al, 2013). The research processes for production, systematization data analysis have been based on semi-structured interviews, document analysis, direct observation, and systematic field notes. The complex realities that were encountered have been comprehensively focused and contextualized in group-discussions with the researches protagonists. The movements and moments of interaction as enhanced by the Pedagogy of Alternation where central. The presence of peasant families in the Agricultural Family School in Olivânia, contributes to the promotion of their self-esteem, regardless of changes that render in the Valley, it generates new forms of self-representation, creates new perceptions of its reality, values the knowledge generated in the relations of peasants ancestries, extends strategies for new spaces of community action and reconstructio of their "peasant ethos".